Predicting matrix failure in composite structures using a hybrid failure criterion. (March 2016) - Chowdhury, Nayeem Tawqir; Wang, John; Chiu, Wing Kong; Yan, Wenyi
Abstract: Matrix failure in composite structures has not been widely presented in literature. Their failure has often been overlooked due to focus directed at fiber failure. With increasing attention on progressive damage models for composite structures it is important that matrix failure is well understood as this is often the characteristic of initial failure in these advanced materials. In this paper the authors perform several four point bend tests on a typical stacking sequence used in composite structures [−45/0/45/90]2S . Inspection techniques involving a FLIR thermal camera are used to detect matrix failure. Two methods are then employed to establish a suitable failure criterion to predict matrix failure. The first compares several failure criteria at the lamina level, whilst the second uses micromechanical analysis to predict matrix failure. It was found that matrix failure was poorly predicted at the lamina level, whilst a hybrid failure criterion incorporating the 1st Stress Invariant and Drucker–Prager failure criterion at the micromechanical level gave a much better prediction. The proposed hybrid failure criterion can be used in various progressive damage models to give a better prediction of initial failure in composite structures.